Internal Validation of the Warwick-Edinburgh Mental Wellbeing Scale:Rasch Analysis in the Indonesian Context - Dimas Aryo Wicaksono; Adiyo Roebianto; Bambang Sumintono (Universitas Ahmad Dahlan, 2021)
This study's purpose is to analyze the psychometric properties of the Indonesian version of the Warwick-Edinburgh Mental WellBeing Scale (WEMWBS) using the Rasch model measurement analysis to test its reliability of measurements, item fit statistics, rating scale functions, and differential item functioning. A total of 855 Indonesian samples completed 14-items in the Indonesian version of WEMWBS. The Rasch analysis indicates that the data fit the model, the item-person reliability is above 0.8, and the item-person separation is above the minimum requirement.Â All items in the instrument have met the statistic criteria indices in terms of outfit mean square as all item-measure correlation is above 0.4.Â The Likert rating scale analyses found the scale functioning properly and free from disordered thresholds. Lastly, DIF by gender was detected in three items. Further testing and refinement need to be conducted to ensure the reliability of the Indonesian version of WEMWBS.Keywords: Mental Well-Being, WEMWBS, Validation, Rasch model, DIF.